Effect of Coupling Medium Temperature on Rate of Intramuscular Temperature Rise Using Continuous Ultrasound - Oshikoya, Corey A. (2000)
OBJECTIVE: We determined the effects of coupling medium temperature on the rate of intramuscular temperature rise (RTR) during continuous ultrasound. DESIGN AND SETTING: Ultrasound was applied in a continuous mode at a frequency of 1 MHz and intensity of 1.5 W/cm². Each subject received 3 treatments, using water-based coupling gel at temperatures of 18°C, 25°C, and 39°C. All treatments were performed in an athletic training room under controlled environmental conditions. SUBJECTS: Eighteen healthy male subjects (mean age = 23.6 ± 3.5 years; height = 177.8 ± 6.9 cm; weight = 76.6 ± 8.2 kg; calf size = 37.6 ± 2.4 cm) participated in this study. MEASUREMENTS: A thermistor was inserted into the left medial triceps surae at a depth of 5 cm, and baseline tissue temperatures were recorded before treatment. Intramuscular temperature was recorded every 30 seconds until the temperature rose 4°C above baseline or until discomfort was felt. RTR was calculated by dividing the absolute temperature change by treatment time. RESULTS: A 1-way, repeated-measures analysis of variance revealed a significant difference in RTR among gel temperatures, RTR was significantly faster using the 25°C gel compared with the 18°C and 39°C gels. There was no difference between the 18°C and 39°C gel treatments. CONCLUSIONS: These results suggest that the use of a cooled or heated gel may be counterproductive when maximal thermal effects are desired within a given time frame.